Physical-maturation with health education on the incidence of anemia among adolescents who married at a young age - Desta Ayu Cahya Rosyida; Nyna Puspita Ningrum; Nina Hidayatunnikmah; Solichatin Solichatin (International Journal of Public Health Science (IJPHS), 2026)
Physical maturity and the incidence of anemia in adolescents who marry at a young age have an impact on the biological and physiological unpreparedness of the adolescent body that is not yet fully mature against the increased risk of anemia, especially in early pregnancy. The solution in this paper provides health education and increased awareness of the dangers of early marriage to physical health, especially the risk of anemia. Nutrition intervention programs and iron supplements for adolescent girls. The purpose of this study was to evaluate the effect of physical maturity on the incidence of anemia in adolescents who marry at a young age. Quantitative research method with quasi-experimental pre-post test design with control group. The population of the study was 54 young women who were married at a young age. The sample size of 44 respondents. Sampling was done using the accidental technique. Data were analyzed using the Chi-square test. The difference in mean hemoglobin levels in adolescents before and after the intervention was analyzed using the paired t-test. Based on the results of statistical test, a p-value of 0.000 was obtained (p-value ≤ 0.05), which indicated that the difference was statistically significant.